Analysis of the UNIX Operating System and improvement of the Password Authentication Technique - Aryan Pratap Singh (Global Journal of Computer Science and Technology, 2024)
The UNIX operating system is an operating system that safeguards against illegal access and other threats to the computer system In this paper the UNIX file system is analyzed the security weaknesses are x-rayed an improved on-time password authentication technique is presented and the underlying model used for the design is described Moreover a password authentication programme was designed which implements an improvement of the general one-time password technique Passwords which are individually selected by users from a codebook are now randomly selected by the system for the user in the improved programme Real-data entries into the programme demonstrate an enhancement of the security of the system even on the event of the loss of the codebook